Time and philosophy : a history of continental thought - McCumber, John (Acumen, 2011)
Looking at the development of continental philosophy in both Europe and America, McCumber discusses philosophers ranging from Hegel, Marx, Kierkegaard, Nietzsche, Husserl, Heidegger, Arendt, Adorno and Horkheimer, Sartre, de Beauvoir, Foucault, and Derrida to the most influential thinkers of today - Agamben, Badiou, Bulter, and Ranciere. Throughout, McCumber's concern is to elucidate the primary texts for readers coming to these thinkers for the first time, while revealing the philosophical rigour that underpins and connects the history of continental thought.